A combined molecular typing approach does not discriminate Legionella pneumophila serogroup 1 strains of a predominant sequence-based type in Palermo, Italy - Celestino Bonura; Caterina Mammina; Antonietta Vella; Santina Belfiore; Alfredo Chiarini; Anna Giammanco (Elsevier, 2009)
Summary: The sequence-based type 1,4,3,1,1,1 of Legionella pneumophila sg.1 is predominant in the Palermo city environment since several years. In this study, extended sequence-based typing and pulsed field gel electrophoresis were used in a combined approach in the aim to enhance discriminatory power of the molecular typing procedures. However, probably due to a common environmental reservoir and genetic stability, most of the strains circulating in the geographic area under study belong to the same clone and are, consequently, indistinguishable by molecular typing. Investigations of clinical cases and tracing to their environmental source require caution and support from sound epidemiological data. Keywords: Legionella pneumophila, Molecular typing, Epidemiology, SBT, PFGE